Clinical Application of the Provox® NiD™ Voice Prosthesis: A Longitudinal Study - Lewin, Jan S. (2013)
OBJECTIVE: To evaluate the indications, complications and device life of the Provox® NiD™ in a large cohort at a tertiary U. S. cancer center. STUDY DESIGN: Longitudinal retrospective cohort study. METHODS: We reviewed the records of patients who used the NiD™ prosthesis (2005–2011) for general indicators, device life, and complications. RESULTS: 186 patients who used the NiD™ were included (median follow-up: 21.4 months). The NiD™ was placed at initial fit in 41 (22%) patients, whereas 145 (78%) tried an NiD™ after using another type of prosthesis. Most patients used the NiD™ similar to an indwelling device. Median NiD™ device life was significantly longer than that of other non-indwelling prostheses (45 vs. 29 days, p=0.0061), and did not significantly differ from that of standard indwellings (45 vs. 50 days, p=0.4263). Thirty-eight percent (71/189) of NiD™ users had a history of early leakage (<8 weeks) using a different prosthesis before trying the NiD™. Among patients with a pre-existing history of early leak, almost 90% of NiD™ prostheses out-performed device life of other products. CONCLUSION: The NiD™ prosthesis offers satisfactory device life, on par with indwelling prostheses in our cohort of NiD™ users. Coupled with favorable published airflow characteristics and satisfactory TE voice, these data suggest that the NiD™ offers a durable, low-cost prosthetic alternative in contemporary practice. A unique indication for NiD™ may be improved device life in some patients with a history of early leakage.